The entrance as a complex ecotone in a Neotropical cave - Prous, Xavier; Lopes Ferreira, Rodrigo; Jacobi, Claudia (International journal of speleology, 2015)
Cave entrances are transition zones with intermediate characteristics between epigean environments, which bear lower environmental stability, and hypogean environments, with lower food resources. Associated to these interfaces there is a specific community, capable of exploiting its unique and intermediate characteristics. This work investigated this community in a Brazilian limestone cave, identifying its arthropod species composition and spatial distribution, and exploring its relationships with climatic and structural environment characteristics and trophic relations. An ecotone zone was identified, with 55 species found only in the ecotone, 49 species were shared with the epigean community, 37 species with the hypogean community, and 14 species were found in the three communities. Although detritus is the base of the trophic web in the entrance, light allows the establishment of some producers and even herbivores. Species diversity in the ecotone was intermediate to that of the adjacent environments. Light is the main filter that acts near the cave entrance and determines the presence and distribution of several species in the ecotone. Therefore, this region is important for the cave ecosystem as a whole, considering that a considerable amount of trophic resources is transferred from the epigean to the hypogean environment through this area. Accordingly, conservation and management strategies regarding cave communities should incorporate actions to study and protect ecotonal communities.